6‐Gingerol‐rich fraction from Zingiber officinale ameliorates carbendazim‐induced endocrine disruption and toxicity in testes and epididymis of rats. (22nd August 2016) - Salihu, M.; Ajayi, B. O.; Adedara, I. A.; de Souza, D.; Rocha, J. B. T.; Farombi, E. O.
Summary: This study evaluated the protective effects of 6‐gingerol‐rich fraction (6‐GRF) from Zingiber officinale on carbendazim (CBZ)‐induced reproductive toxicity in rats. Adult male rats were treated with either CBZ (50 mg/kg) alone or in combination with 6‐GRF (50, 100 and 200 mg/kg) for 14 consecutive days. Gas chromatography–mass spectrometry (GCMS) analysis revealed that 6‐GRF consists of ten bioactive chemical components with 6‐gingerol being the most abundant (30.76%). Administration of 6‐GRF significantly ( p < .05) prevented CBZ‐mediated increase in absolute and relative testes weights as well as restored the sperm quantity and quality in the treated rats to near control. In testes and epididymis, 6‐GRF significantly abolished CBZ‐mediated increase in oxidative damage as well as augmented antioxidant enzymes activities and glutathione level in the treated rats. Moreover, CBZ administration alone significantly decreased plasma levels of testosterone, thyrotropin, triiodothyronine and tetraiodothyronine, whereas follicle‐stimulating hormone was significantly elevated without affecting luteinising hormone and prolactin levels when compared with the control. Conversely, 6‐GRF ameliorated the disruption in the hormonal levels and restored their levels to near normalcy in CBZ‐treated rats. Collectively, 6‐GRF inhibited the adverse effects of CBZ on the antioxidant defence systems, hormonal balance and histology of the testes and epididymis in rats.